The mediating effects of perceived usefulness and perceived ease of use on nurses’ intentions to adopt advanced technology - Abid Hussain; Ma Zhiqiang; Mingxing Li; Arif Jameel; Shahida Kanwel; Saif Ahmad; Bailin Ge (BMC Nursing)
Abstract This study explored the role of technology systems in influencing nurses’ intentions to adopt medical applications that enhance their performance and how technology contributes to improvements in hospital systems. The study examines the intention to use technology through the mediating effects of perceived usefulness and perceived ease of use, with technology sophistication. A random sampling method was employed to gather 687 responses from nurses. The statistical analysis was conducted using AMOS version 25.0 and SPSS. The findings indicate a significant association between technology sophistication (TS), perceived usefulness (PU), perceived ease of use (PEU), and intention to use (IU). Additionally, PU and PEU positively mediate the relationship between TS and IU. This research will benefit policymakers aiming to enhance nurses’ performance by adopting modern technology. Authorities should consider introducing advanced technology systems to meet the goals of hospital administration and support nurses effectively.